Sistem Informasi Persediaan Barang Berbasis Web pada Usaha Elektronik Mitra Com - Aryan Fauzi; Khairuman; Mukhroji (LPPM Politeknik Aceh Selatan, 2026)
An inventory information system is important for helping Micro, Small, and Medium Enterprises (MSMEs) manage stock data accurately and efficiently. MSME Mitra Com still uses manual stock recording, which often causes data errors, delays in reporting, and difficulties in monitoring inventory conditions. This study aims to develop a web-based inventory information system to support stock management activities at MSME Mitra Com. The research method used is software engineering with a qualitative descriptive approach. The research stages include system requirement analysis, system design using Unified Modeling Language (UML), system implementation using PHP and MySQL, and system testing using the Black Box Testing method. The results show that the developed system can manage item data, record incoming and outgoing goods, and generate inventory reports automatically. The system helps improve work efficiency, reduce recording errors, and support decision-making at MSME Mitra Com.